Development of Non-Enzymatic Glucose Sensor Using Ag-Au Bimetallic Modified Pencil Lead Electrode with Voltammetry Method - Marlini, Rahmida; Kumala Sari, Trisna; Alizar, Alizar; Dwipa Yamesa Away, Romy (Indonesian Journal of Chemical Analysis (IJCA), 2025)
Glucose is an essential monosaccharide that serves as the main source of energy in the human body. An imbalance in glucose levels in the body can lead to serious metabolic disorders, such as diabetes mellitus. Therefore, effective methods of analyzing and monitoring glucose levels are needed for early detection and more optimal disease management. In this study, a non-enzymatic glucose sensor based on Pencil Lead Electrode (PLE) modified with silver-gold (Ag-Au) bimetallic was developed through electrodeposition method using cyclic voltammetry. This modification aims to improve sensitivity and cost efficiency in glucose detection compared to enzymatic sensors, that are susceptible to denaturation and higher production costs. Electrodeposition is performed in a potential range of 1.6 V to -0.4 V to obtain an optimal bimetallic coating on the PLE surface. The Ag-Au/PLE electrode provided the best electrochemical response in detecting glucose, with oxidation and re-oxidation peaks at +0.01 V in 0.1 M KOH as a supporting electrolyte. The optimal condition was obtained in five electrodeposition cycles, with a correlation coefficient value of 0.9984 and a detection limit of 0.206 mM, indicating high sensitivity and accuracy. These results indicate that Ag-Au/PLE electrodes have great potential as reliable, sensitive and economical non-enzymatic glucose sensors.